(untitled) (International Journal of Engineering and Computer Science, 2017)
This paper formulates a problem for production plan as k- most demanding products (k-MDP). Given a set of customers demanding a certain type of products with multiple attributes, a set of existing products of the type, a set of candidate products that company is able to offer, and a positive integer k, it helps the company to select k products from the candidate products such that the expected number of the total customers for the k products is maximized. One greedy algorithm is used to find approximate solution for the problem. Attempt is also made to find the optimal solution of the problem by estimating the expected number for the total customers of a set of k candidate products for reducing the search space of the optimal solution.